The intestinal microbial community and function of Riptortus pedestris at different developmental stages and its effects on development - Yanbin Wang; Rong Li; Chunjing Wang; Ting Sun; Hongjuan Zhang; Fang Zhao; Jiehui Liu; Yuqiong Hao; Xiansheng Xie (Frontiers in Microbiology)
IntroductionRiptortus pedestris is a destructive pest that threatens multiple leguminous crops in China. The intestinal microbiota plays a crucial role in the growth and reproduction of host insects. However, the composition and function of the gut microbiota at different developmental stages remain unclear.MethodsHere, metagenomic sequencing was performed to clarify the gut microbial diversity and function in 2nd-, 3rd-, 4th-, and 5th- instar nymphs (2 N–5 N) and female adults (FAs) of R. pedestris and the effects of vital gut bacteria on development was detected. The gut bacteria have the stage specificity, indicating their function in the development of R. pedestris.ResultsEnterococcus and Caballerronia were the predominant bacteria present during the development of the 2 N–FAs. In addition, the microbial abundances in the 3 N and 4 N guts were significantly greater than those in the others guts. Furthermore, 5 N harbored the abundant microbiota Burkholderia-Paraburkholderia-Caballeronia. The metabolic pathways were significantly enriched from 2 N to FAs. Carbohydrate metabolism, including glycoside hydrolases (GHs) and glycosyl transferases (GTs), occurs throughout the entire developmental stage. Many antibiotic resistance genes (ARGs) were detected from 2 N to FAs. The bacteria from Pseudomonadota and Bacillota presented a broad spectrum of antibiotic resistance. Excitingly, Burkholderia bacteria eliminated by antibiotic treatment were unable to molt normally, and their lifespan was shortened in nymphs, indicating that the gut microbiota had a significant effect on nymph development.ConclusionIn summary, our results, for the first time, systematically illustrate the abundance and function across the gut microbiota from the different developmental stages of R. pedestris and demonstrate that the genera Burkholderia are crucial during the development of R. pedestris. This study provides the basis for stinkbug management strategies that focus on the pivotal gut microbiota.